Rancangan Pembelajaran Matematika Pada Kelas Inklusif - Fatimah Azhara; Ariantje Dimpudus (Lembag, 2024)
Learning mathematics is one of the subjects in school. Negative assumptions about mathematics are one of the reasons for difficulties in learning it. This research discusses the importance of teacher readiness in the mathematics learning process in inclusive classes. This readiness includes the preparation of a Learning Implementation Plan (RPP) carried out by teachers by adapting to the needs of all students, including children with special needs (ABK). This research uses the library study method to collect information from various sources, including journals, books and government documents. Inclusive education aims to provide fair educational services for all students, including ABK, by adjusting the curriculum and appropriate learning methods. Special assistant teachers (GPK) play an important role in accompanying and assisting ABK during the learning process. This research highlights the importance of modifications in preparing lesson plans and implementing appropriate interventions to support successful mathematics learning in inclusive classes. RPP adjustments are made by adding notes to the adjusted components, ensuring there is no discrimination against students with special needs. This research shows that inclusive education can increase access to education for all children, including those with special needs, so that they can learn together in a friendly and supportive environment. This research provides insight into the importance of learning modifications and collaboration between class teachers, GPK, and parents to create an inclusive and effective learning environment for ABK.